1982
DOI: 10.1111/j.1471-4159.1982.tb08702.x
|View full text |Cite
|
Sign up to set email alerts
|

The Regional Concentrations of S‐Adenosyl‐l‐Methionine, S‐Adenosyl‐l‐Homocysteine, and Adenosine in Rat Brain

Abstract: The concentrations of S-adenosyl-L-methionine (SAM), S-adenosyl-L-homocysteine (SAH), and adenosine (Ado) were determined in whole brain and rat brain regions by HPLC. The whole brain contains, respectively, 22 nmol, 1 nmol, and 65 nmol of SAM, SAH, and Ado per g of wet tissue. Their distribution indicated that SAM and SAH levels are highest in brainstem, whereas the Ado level is highest in cortex. With aging the SAM concentrations decrease in whole brain, brainstem, and hypothalamus (-25%) and SAH levels incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
30
1

Year Published

1989
1989
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(34 citation statements)
references
References 35 publications
3
30
1
Order By: Relevance
“…The levels of SAM and SAH measured in our experiments were consistent with those reported by others in postnatal rats (65,66). In adult animals, choline-(19) or methyl-deficient diets (67) lowered hepatic SAM levels, and rats that were fed a diet supplemented with methionine, choline, folic acid, and vitamin B 12 had increased hepatic levels of SAM (18).…”
Section: Discussionsupporting
confidence: 81%
“…The levels of SAM and SAH measured in our experiments were consistent with those reported by others in postnatal rats (65,66). In adult animals, choline-(19) or methyl-deficient diets (67) lowered hepatic SAM levels, and rats that were fed a diet supplemented with methionine, choline, folic acid, and vitamin B 12 had increased hepatic levels of SAM (18).…”
Section: Discussionsupporting
confidence: 81%
“…ADA activity decreased with age in the cortex and hippocampus [131], which may induce an increase in Ado levels in elderly people. Indeed, concentrations of Ado exhibit age-dependent alterations in the human cerebral cortex (Ado concentration was higher in the elderly compared with middle-aged subjects) [57] and in all areas of the rat brain [132]. The highest level of SAH in the rat striatum and its modification by age has also been demonstrated [132,133], suggesting that SAHH activity is also unevenly distributed and may change with age in the brain.…”
Section: Modulation Of Adenosine Levels and Epileptic Activity By Metmentioning
confidence: 99%
“…These changes may be correlated with varia tions in concentrations of S-adenosyl-L-methionine and S-adenosylhomocysteine. The endogenous SAM level was higher and the SAH level lower in newborn compared with adult rats [20,22], These data suggested that Several reports have studied the ontogen esis of adenosine Ai sites in rat forebrain. Marangos et al [16] showed that high-and low-affinity sites appear to develop in paral lel and the increase of [3H]-CHA binding observed was apparently due to an increase in the number of both high and low affinity rather than to changes in the kinetic of bind ing.…”
Section: Discussionmentioning
confidence: 68%
“…Whole forebrains, cortex or striata used for analysis of SAM, SAH and adenosine concentration, were treated and analysed by high-performance liquid chro matography (HPLC) as previously described [22],…”
Section: Determination Of Sam Sah and Adenosine Levelsmentioning
confidence: 99%